The Effect of Mangosteen Peel Extract on Sperm Motility and Sperm Count of Swiss Webster Mice Induced by Hard Physical Exercise - Ardi Prawira; Stella T. Hasianna; Sylvia Soeng (Universitas Kristen Maranatha, 2015)
High-intensity physical exercises can increase oxidative stress, causing damage to reproductive system. The purpose of this study was to determine the effect of mangosteen peel extract on sperm motility and sperm count of Swiss Webster mice induced by high-intensity physical exercise. This was a real experimental with complete randomized design. Twenty five male Swiss Webster mice were divided into five groups (n = 5). Negative control (KN) was without any treatment, positive control (KP) was given treadmill exercise only, the treatment groups (KM1, KM2, KM3) were given mangosteen peel extract orally 2, 4, 8 mg respectively as well as treadmill exercises. The treadmill exercises was conducted for 35 days. The sperm motility (mm/second) and the sperm count (per mm3) were assessed manually using Improved Neaubauer chamber. The result were analyzed using one-way ANOVA followed by Tukey HSD. The result showed high significant differences of sperm motility and sperm count between KM2 and KP, also between KM2 with KM1 and KM3 (p=0,000). The conclusion was mangosteen peel extract improved the sperm motility and sperm count of Swiss Webster mice induced by high-intensity physical exercise with 4 mg as the optimal dose. Keywords: mangosteen peel, sperm motility, sperm count